PENDEKATAN PENGELOLAAN KURIKULUM DALAM MENCIPTAKAN SEKOLAH UNGGUL - Robiatul Awwaliyah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
This paper describes the Curriculum Management Approach in Creating a Superior School. A superior school is an educational institution that is able to bring each of its students to achieve measurable abilities and be able to demonstrate their accomplishments. To arrive at this stage, there are several components that must be implemented by each school including curriculum management. The curriculum occupies a very strategic position in a school. The curriculum is a guideline in the learning process. However, formulating a curriculum is not an easy job, the use of a curriculum that is not appropriate in a school or madrasah is also a reason why the failure of a school reaches a superior level. There are several approaches that can be implemented as an effort in creating superior schools, namely the subject of academic approach, humanistic approach, social approach, and competency approach. Keywords: Superior schools, curriculum management, curriculum approach